The Impact of Government Policies on Competitiveness of Rice Farming in Purbalingga Regency - Asti Nur Afifah; Masyhuri Masyhuri; Any Suryantini; Lestari Rahayu Waluyati (Agro Ekonomi, 2019)
Rice is a potential food crop to be developed in Purbalingga Regency, so it is necessary to know its competitiveness so that rice production can be increased. This study aims to (1) determine the competitiveness of rice farming in Purbalingga Regency, and (2) determine the impact of government policies on rice farming in Purbalingga Regency. It used the Policy Analysis Matrix (PAM) as the research method. The research sample was purposively selected from Bukateja Subdistrict because it is the region with the highest rice production in Purbalingga Regency. It used the data of rice farming collected in two seasons, such as MT I (rainy season) and MT II (dry season) with a total sample of 80 rice farmers. The analysis showed that rice farming in Purbalingga Regency in MT I (rainy season) and MT II (dry season) had good level of competitiveness because they had competitive advantages and comparative advantages. The impact of government policies on rice farming output and input for both tradeable and non-tradeable inputs are significant. The government also has applied protective rice farming input-output policy. Based on this research, it is suggested that there is subsidy to improve irrigation networks and subsidy to purchase of modern inputs (agricultural machinery) to increase rice productivity and raise the competitiveness of rice farming in Purbalingga Regency as well as the government needs to maintaining the rice import tariff policy, determining the basic price of rice, and providing input subsidies such as chemical fertilizer.